Traffic aware channel assignment with node stability in wireless mesh networks - JasmineDavid, D.; Jegathesan, V. (International Journal of Engineering and Technology, 2018)
In a wireless network the most challenging issue is Channel assignment. The channel assignment problem is codependent with the routing problem. We need to compute again the channel assignment as and when the traffic pattern changes. Anyways, previously followed channel assignment algorithms will assign channels from scratch. It will end up with an entirely dissimilar configuration of nodes; in turn it will disturb the action of the particular network. It takes little time to create links and to establish new channels. This time is significant in assigning links for wireless networks. This leads to channel reassignment. This algorithm considers the existing channel assignment and tries to go along with the new stream of traffic flow design in the finest possible way by changing the channel on a restricted number of radios. In order to provide node stability, we used entropy function. In this paper, we demonstrate a channel reallocation algorithm with node permanency and appraise its performance by using NS2. Experimental outcomes show that the node stability can progress the performance of network when compared with the earlier methods.Â